The effect of the acute inflammatory response of burns and its treatment on clot characteristics and quality: A prospective case controlled study. Issue 5 (August 2020) - Marsden, N.J.; Lawrence, M.; Davies, N.; Davies, G.; Morris, K.; Williams, P.R.; Whitaker, I.S.; Evans, P.A.
Highlights: Coagulopathy following burns leads to increased morbidity and mortality. Current markers of coagulation in acute burns have their limitations. Clot microstructure is significantly altered during the first 24 h. Consistent with a hypocoagulable state, not identified using current techniques. Colloid fluid therapy may play a role in producing these changes. Abstract: Introduction: Burns are known to have an effect on coagulation in the early period after burn. Current coagulation tests have been criticised in acute burns due to their inherent limitations. This study aims to investigate the potential for a new quantitative functional biomarker of clot quality, fractal dimension, to identify changes in clot microstructure as a result of the burn inflammatory response and its treatment. Methods: A total of fifty-eight burn patients were included in this prospective case-controlled study. The control group (29 patients mean TBSA 1%), and case group (29 patients mean TBSA 30%) were compared at baseline and the case group investigated further over four time points (baseline, 12 h, 24 h and 5–7 days). Fractal analysis was performed, as well as current markers of coagulation, inflammatory markers and point-of-care tests, Thromboelastography and Multiplate analysis. Results: Fractal dimension did not differ between groups at admission (1.73 ± 0.06 and 1.72 ± 0.1), and fell within the healthy index normal range (1.74 ± 0.7), suggesting a normal clot microstructure in the early period after burn. Fractal dimension significantly reduced from baseline over the first 24 h following injury (1.59 ± 0.03 p < 0.005), indicating a significant reduction in mechanical clot strength and functionality consistent with a hypocoagulable state, not identified with other markers. Conclusions: This is the first study to quantify the changes in clot microstructure following burn injury. This study confirms clot microstructure is significantly altered during the first 24 h after burn, with the production of a weaker, more porous fibrin clot, consistent with a hypocoagulable state.